Seminal plasma Oxidative stress (MDA) and Total antioxidant capacity (TAC) its clinical relation to testosterone and prolactin hormon in oligozoospermia men - Salih, Ammar Talal; Alwafi, Haider Abdul-Kareem Mohammad; Khosho, Edwar Zeya (American Journal of Bioscience and Clinical Integrity, 2026)
This case-control study aimed to investigate the relationship between reproductive hormones, oxidative stress markers, and antioxidant capacity in men with oligozoospermia. A total of 200 participants were enrolled, comprising 100 oligozoospermic men and 100 fertile controls. Seminal levels of malondialdehyde (MDA) and total antioxidant capacity (TAC) were assessed alongside serum concentrations of testosterone, prolactin, luteinizing hormone (LH), follicle-stimulating hormone (FSH), and estradiol. Compared to controls, the oligozoospermic group exhibited significantly higher oxidative stress, as indicated by elevated MDA levels (p<0.001), and significantly lower antioxidant capacity, reflected by reduced TAC levels (p<0.001). Hormonal analysis revealed significantly increased testosterone (p<0.001) and decreased prolactin (p<0.001) levels in infertile men. Strong inverse correlations were observed between MDA and testosterone, as well as between TAC and prolactin. These findings suggest that oligozoospermia is associated with a distinct biochemical profile characterized by heightened oxidative damage, impaired antioxidant defense, and altered endocrine regulation. The study highlights the potential clinical utility of integrating oxidative and hormonal biomarkers for a more comprehensive diagnostic approach to male infertility, reflecting its multifactorial pathophysiology.